Measuring hedonic appeals and individual hedonic orientations in female consumption of status products - Teo, Carol Boon Chui; Md. Sidin, Samsinar (Institute of Business Excellence and Faculty of Business Management, Universiti Teknologi MARA (UiTM), 2010)
Marketers today acknowledege that the female consumer segment has emerged and is shaping the future markets. They are seeking status by way of consumption of status appealing products and seeking hedonism from consumption. This study explores female hedonic orientations in their effort of seeking status and hedonic values attached to status products. The outcome is to develop scales to measure interest to consume hedonically. The study utilizes qualitative and quantitative approach to develop the scales. Three studies were conducted. The preliminary study was to identify three status product classes (shopping, specialty and credence service) consumed by female consumers followed by focus group discussions to generate items to measure hedonism in products and individual behavior. The final study was a survey on 444 working females to test the validity of the status product hedonism scale and female hedonic orientation scale. Product hedonism generated includes imaginal-emotion for holiday vacation, voyeurism pleasures for dressing and symbolism for jewellery. Individual hedonic orientation yielded extrovert behavior, emotional attachment to product, exhibitionism, uniqueness and excitement seeking pleasures of females. The scale were subject to exploratory and confirmatory factor analysis to derive model fit using SEM. Findings show both scales had adequate model fit with acceptable internal consistency, construct rel iability and divergent validity. Some implications for research and marketing were explained.